Copper Regulates the Susceptibility of Zebrafish Larvae to Inflammatory Stimuli by Controlling Neutrophil/Macrophage Survival - Chen, MingYue; Luo, Yi; Xu, JiangPing; Chang, Ming-Xian; Liu, Jing-Xia (Frontiers in Immunology, 2019)
Copper has been revealed to negatively affect the hematopoietic system, which has an important function in immune pathogen defense, but little is known about the potential mechanism. In this study, copper stressed larvae exhibited significantly increased mortality as well as reduced percentages of GFP-labelled macrophages and neutrophils after Aeromonas hydrophila (A. hydrophila) infection. However, those copper-stressed GFP-labelled macrophages and neutrophils showed more rapid responses to A. hydrophila infection. The transcriptional profiles in copper stressed macrophages or neutrophils were unveiled by RNA-Sequencing, and KEGG pathway analysis revealed enrichment of differentially expressed genes (DEGs) in lysosome, apoptosis, oxidative phosphorylation, phagosome, etc.. The copper stressed macrophages or neutrophils were revealed to have an increase in reactive oxygen species (ROS) and mitochondria ROS (mROS)-mediated apoptosis, and a reduction in phagocytosis. Furthermore, the A. hydrophila-infected copper-stressed macrophages or neutrophils were found unable to maintain a consistently increased expression in immune responsive genes. This study demonstrated for the first time that copper might induce the susceptibility of fish larvae to inflammatory stimuli via triggering macrophage or neutrophil apoptosis, leading to reduced phagocytic activities and non-sustainable immune responses in immune macrophages or neutrophils.